Analysis of 3-Phase Induction Motor at Chiller Room FKAAB Building Using Motor Current Signature Analysis and Vibration-Monitoring - Norrawai, Muhammad Fahmi; Mohd Yousof , Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2022)
Both synchronous and induction motors have been used in chiller systems. The chiller system which consists of pumps, compressor and fans is driven by AC motors. Induction motors are commonly applied in modern chiller systems, however synchronous reluctance motor (SynRM) is a relatively recent high-efficiency motor technology, according to Felipe Oliveira and Abhisek Ukil in their research paper Comparative Performance Analysis of Induction and Synchronous Reluctance Motors in Chiller Systems for Energy Efficient Buildings. In this context, early detection of fault is necessary and very important to reduce maintenance costs. The main objective of this project is to monitor the condition of the three-phase induction motor by using different techniques. The sub-objectives are to measure line current of low voltage motors at chiller room building, to measure vibration signal of low voltage motors at chiller room building and to analyse motor current signature and vibration frequency spectrum of low voltage motors. The induction motors for the chiller system have been analysed based on the motor current signature analysis (MCSA) and vibration analysis. There are 2 motors in total which are a motor for condenser water pump 1 and a motor for chilled water pump 1. The results indicate that the 2 motors have broken rotor fault by using MCSA technique. For the vibration analysis technique, there are various faults that can be assumed. For example, angular misalignment, bent shaft, mechanical looseness, cavitation, turbulence and electrical problem. The findings and recommendations of this study are obtaining the induction motor’s handbook or datasheets can help in the detection of many other faults of the motor. This project was performed only on three induction motors for the chiller system located at the FKAAB building. Therefore, performing the same measurement for another chiller system in UTHM main campus would be interesting.